Modelling lithium ion battery remaining capacity - Peng, Li (2016)
Normally, Batteries have their own useful cycle and useful life before going to the limit of their End-Of-Life(EOL). If we want to maximize the battery’s lifespan, we must go through a sequence of charging and discharging cycle. So we can avoid overcharge or overdischage. A very important pareameter we need to estimate is state of charge(SOC), because there is no direct measurement on it. The result of estimated SOC is the key to calculate battery remaining life or total lifespan. Failure of SOC estimation will lead to bad performance of battery and thus, shorten the lifetime of the battery. This report have some discussions on different techniques to estimate the SOC of battery(open-circuit voltage method, coulomb counting method and extended Kalman filter algorithm). Then a battery remaining life prediction model can be used to estimate remaining capacity of battery after using for a period of time. Lastly, the total battery lifetime or remaining life can be calculated.